The Relationship Between Marriage Satisfaction and Anxiety of Pregnant Women in Facing Childbirth - Rahmawati, Veronica Yeni; Rithpho, Pratuma; Puspasari, Jehan; Fitria, Dian (STIKES Adi Husada, 2024)
The birth process is interpreted by a mother as a difficult process and full of struggle so it causes anxiety for pregnant women in facing childbirth. Excessive anxiety has a negative impact on the birth process and even causes birth complications. This study aimed to determine the relationship between marriage satisfaction and the anxiety of pregnant women in facing childbirth. This research used a cross-sectional method and the number of pregnant women in the Central Jakarta area with a sample size of 110 people. The research instrument used the Pregnancy-Related Anxiety Questionnaire-Revised 2 (PRAQ-2) questionnaire and the Marital Adjustment Test (MAT) questionnaire. In this study, data analysis used the Spearman Rho test. The results of this study show that there is a significant relationship between marriage satisfaction and anxiety about facing childbirth (p value=0.036). Marriage satisfaction has a fairly large influence on pregnant women's anxiety in facing childbirth in the moderate category (R Square=0.051). The role of the maternity nurse is to be able to take preventive measures to reduce the heavy or excessive anxiety of pregnant women through mentoring and counseling programs together with the family, especially the husband.